The Impact Influencers Have on the Buying Habits of Individuals - Deatherage, Isabella (East Carolina University, 2022)
Social media has given rise to a new type of celebrity, commonly known as an “influencer.” An influencer, in theory, influences the opinions of others, but how much of an influence do they actually have? This study analyzes the true power over people’s opinions these micro-celebrities possess. Through a survey of 278 individuals, comments on posts, and looking at purchase trends it was determined the impact. The study found that people want to trust who they are buying from, and they feel a higher level of trust from these individuals. The findings reflect that people will change their opinions, purchase products, and listen to influencers.
Keywords: Influencers, Social Media, Impact